Comprehensive Review of the Role of Radiology in Guiding Surgical Interventions: Bridging Imaging, Anesthesia, and Nursing - Alwushayh , Alwaleed Abdullah; Alanazi , Yasir Mandi Jadid; Al-Ruwaili , Jamilaha Ali A geel; Alazmi , Mohammed Obaid; Alazmi , Majed Sayah; AlAzmi , Hamad Sulaiman K; Alhumaidi , Abdalhameed Mohammad; Alsharari , Jamal Atallah; Alruwaili , Menwar Subair; Alshammari , Abdullah Mohammed; Alsharari , Duaa Mohammed; Mufadhi , Fahad Saleh; et al. (Journal of Ecohumanism, 2024)
Radiology has positively impacted surgical procedures in that better imaging is available to guarantee the accuracy and effectiveness of the procedures. This review focuses on radiology’s preoperative, intraoperative, and postoperative roles and suggests synergism with anesthesia and nursing. This convergence brings imaging and surgery, surgery planning, and postoperative care, and makes radiology improve accuracy, reduce complications, and extend recovery. The review also assesses the historical trend in imaging developments, currently existing technology, and the cross-disciplinary environment facilitating their connection. Major objectives of the study include the role of radiologically assisted operations and their effects on effectiveness, security, and teamwork. Training suggestions, practical methodological implementation issues, and future research implications are made.